Difusi Inovasi dalam Penggunaan Kalkulator Hijau: Peran Bank Indonesia dalam Mendorong Keberlanjutan - Pinda, Pinda; Cahyati, Ega; Husna, Amhara; Hafizh, Farhat; Mahdalena, Vina (Fakultas Pertanian, Universitas Lampung, 2025)
This study examines the diffusion of innovation in the use of the Green Calculator, developed by Bank Indonesia to support sustainability and reduce carbon emissions in the financial sector. The background of the study is the urgent need to mitigate the effects of climate change, as well as Indonesia’s commitment to reducing greenhouse gas emissions. The research aims to analyze Bank Indonesia's strategic role in accelerating the adoption of eco-friendly technologies in the banking and business sectors. The research method used is qualitative descriptive, analyzing secondary data from various relevant policies and regulations. The findings show that the Green Calculator facilitates accurate carbon emission calculations; however, its adoption faces challenges such as low awareness and technical limitations among businesses. In conclusion, while the diffusion process encounters obstacles, there are significant opportunities to accelerate adoption through increased awareness and economic incentives for users.